MARRIAGE AGE LIMIT PROVISIONS REVIEWED FROM THE LAW LAW NUMBER 16 YEAR 2019 ABOUT THE CHANGES TO LAW NUMBER 1 YEAR 1974 CONCERNING MARRIAGE AND LAW TRADITION - Desi Robiatul Adawiyah Siregar; Rosnidar Sembiring; Idha Apriliyana; Yefrizawati Yefrizawati (NOMOI Law Review, 2022)
The stipulation of the age limit for marriage is one of the very important pillars in the legal protection of underage marriages. Underage marriage is a marriage or contract that can guarantee that a man and a woman have each other and can have husband and wife relations, and the marriage is carried out by someone (prospective husband/prospective wife) whose age has not yet reached the age determined by law. currently in force in Indonesia that has been determined by the government. UU no. 16 of 2019 amendments to Law No. 1 of 1974 concerning marriage Article 7, namely "Marriage is only permitted if a man and a woman have reached the age of 19 (Nineteen) years. The method use in this research is normative legal research. The issues discussed are about how the pluralism of the marriage age limit according to positive law and customary law, regarding how to implement Law No. 16 of 2019 concerning Amendments to Law No. 1 of 1974 concerning Marriage, regarding how legal protection is related to age. marriage in which the parties contain Law Number 16 of 2019 amendments to Law Number 1 of 1974 concerning Marriage and customary law.